2015
DOI: 10.1016/j.neurobiolaging.2014.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background influences age-related decline in visual and nonvisual retinal responses, circadian rhythms, and sleep

Abstract: The circadian system is entrained to the environmental light/dark cycle via retinal photoreceptors and regulates numerous aspects of physiology and behavior, including sleep. These processes are all key factors in healthy aging showing a gradual decline with age. Despite their importance, the exact mechanisms underlying this decline are yet to be fully understood. One of the most effective tools we have to understand the genetic factors underlying these processes are genetically inbred mouse strains. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
66
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 55 publications
(83 reference statements)
8
66
0
2
Order By: Relevance
“…Large differences in sleep duration and timing among humans suggests that existing genetic variation among individuals potently affects sleep (Hartmann, 1973;Kronholm et al, 2006;He et al, 2009). While many laboratory studies investigating the molecular mechanisms of sleep regulation have relied on highly inbred model systems including mice, zebrafish and fruit flies, the study of sleep in outbred populations has revealed that geographical location, evolutionary history and naturally occurring genetic variation contribute to robust sleep differences within animals of the same species (DubouĂ© et al, 2011;Zimmerman et al, 2012;Banks et al, 2015;Svetec et al, 2015). Even though sleep has been characterized in surprisingly few evolutionary systems, small, non-mammalian model organisms with a well-defined evolutionary history provide opportunities to identify novel mechanisms underlying sleep regulation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Large differences in sleep duration and timing among humans suggests that existing genetic variation among individuals potently affects sleep (Hartmann, 1973;Kronholm et al, 2006;He et al, 2009). While many laboratory studies investigating the molecular mechanisms of sleep regulation have relied on highly inbred model systems including mice, zebrafish and fruit flies, the study of sleep in outbred populations has revealed that geographical location, evolutionary history and naturally occurring genetic variation contribute to robust sleep differences within animals of the same species (DubouĂ© et al, 2011;Zimmerman et al, 2012;Banks et al, 2015;Svetec et al, 2015). Even though sleep has been characterized in surprisingly few evolutionary systems, small, non-mammalian model organisms with a well-defined evolutionary history provide opportunities to identify novel mechanisms underlying sleep regulation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A recent sequence comparison of B6J and B6N from Taconic Farms showed that these sub-strains differ only in 34 single nucleotide polymorphisms, 2 indels in coding regions and 15 structural gene variants. Despite their genetic similarity, both sub-strains differ in a number of phenotypes including behaviors (Bechard et al 2012;Blum et al 1982;Bothe et al 2004;Bryant et al 2008;Crusio et al 1991;Hager et al 2014;Kumar et al 2013;Matsuo et al 2010;Mogil & Wilson 1997;Mouri et al 2012;Mulligan et al 2008;Ramachandra et al 2007;Siegmund et al 2005;Simon et al 2013;Stiedl et al 1999), circadian rhythms (Banks et al 2014), metabolic functions and responses to high-fat diet (Andersson et al 2010;Heiker et al 2014;Podrini et al 2013;Simon et al 2013;Walker et al 2014), as well as the physiology and pathology of the cardiovascular (Cardin et al 2014;Kararigas et al 2014;Moreth et al 2014), visual (Mattapallil et al 2012;Simon et al 2013) and auditory systems (Kendall & Schacht 2014;Schnabolk et al 2014). These phenotype differences are important, because many studies use genetic mouse models on these two C57BL/6 genetic backgrounds.…”
mentioning
confidence: 99%
“…Despite their genetic similarity e.g. refs 32 and 33 B6N and B6J substrains show differences in a number of behavioral tests, although video-based analysis shows their rest/activity behavior to be indistinguishable at the relevant age 34 . Second, our study used a different EEG electrode configuration, which affects the frequency contributions of the recorded signal.…”
Section: Discussionmentioning
confidence: 99%